Qawlan Ma‘rufa in the Act of Giving Wealth: A Study of Tafsir al-Mizan by al-Ṭabaṭaba’i with an Introduction to Islamic Communication - Hafsah Juni Batubara (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine the meaning of qaulān ma‘rūfa (“kind speech”) in the practice of giving wealth according to Tafsīr al-Mīzān by Muhammad Husain Ṭabāṭabā’ī. The research adopts a qualitative interpretive approach and employs a library research method. To uncover deeper insights, it applies hermeneutic interpretation, thematic analysis, and an intertextual approach. Despite the growing interest in Islamic communication, few studies have explored its epistemological roots in Qur’anic exegesis, particularly in Tafsīr al-Mīzān. This study fills that gap by analyzing how qaulān ma‘rūfa functions not only as a moral injunction but also as a communicative act that reflects compassion, respect, and ethical interaction. The findings reveal that the principle of qaulān ma‘rūfa forms the ethical foundation of social communication—emphasizing sincerity, maintaining human dignity, and avoiding harmful speech. Theoretically, the study contributes to the development of an Islamic communication framework grounded in Qur’anic ethics, while practically, it offers insights for da‘wah communication models that integrate moral and spiritual dimensions. Thus, this research advances the understanding of communication in Islam as a transformative medium for nurturing ethical and compassionate human relations.